Handbook on lexicography for Philippine and other languages with illustrations from the Batad Ifugao dictionary - Newell, Leonard E. (Linguistic Society of the Philippines, 1995)
"This handbook is primarily intended for field linguistics wroking with lesser-known languages for which good lexical descriptions have yet to be compiled." This publication is primarily based on work on Philippine languages. It is also a useful tool and guide for dictionary making as it discussed the science and art of dictionary making. It has tables, figures and an index.